Police Use Of Excessive Force: A Case Study Of Lethal (Deadly) Force - Vedat Kargin (European Scientific Journal, ESJ, 2016)
Two African-American civilians, Sean Bell and Amadou Bailo Diallo, suffered tragic deaths as a result of use of lethal force by the police. This case study presents an in-depth analysis of the determinants that affected the officers’ use of lethal force with regard to the above mentioned cases. In 1999, Amadou Bailo Diallo was killed in a 41-bullet police shooting in New York. Similarly in 2006, Sean Bell was shot to death in a 50-bullet fusillade that involved officers from The New York City Police Department. After the Bell shooting, officers of The New York City Police Department were under investigation. The case study focuses on and examines the similarities and differences of both cases, official and public reactions in the aftermath of the shootings, investigation processes, as well as the indictments of the police officers involved in both cases. Finally, this study proposes some suggestions on the use of excessive force based on the findings of the two specific cases.